The Australian Mid-latitude Continental Ionosphere with Respect to Low-frequency Radio Astronomy - Herne, David Edwin (Curtin University, 2016)
The ionosphere above the Murchison Radio Observatory (MRO) has been characterised over half of solar cycle 24 and its response to impinging low-frequency radio waves described. The outcomes of this thesis will contribute to an operational requirement of the Murchison WideField Array (MWA) radio telescope (calibration) and delivery of the project’s scientific goals (high fidelity imaging) and shows that the MRO site is an excellent location from which to conduct low-frequency radio astronomy.